Accessible Software Design: Thinking Outside the Box - Ortiz, Claudia (2024)
Accessibility is generally approached as an implementation aspect, and people with disabilities are not involved in the early design stages. On the other hand, the rise of Design Thinking has led to a rethink of whether traditional empathy methods (interviews and surveys) capture the real needs of people, particularly those with disabilities. This paper presents an extension of the article published in the XXIX Argentine Congress of Computer Science (CACIC 2023), where an empathising guideline with people with disabilities using Design Thinking experiences was proposed to design accessible software from scratch. In addition, in the article published in CACIC 2023, this empathising guideline is used to design and explore two experiences with two people, one with motor difficulties (in this case affecting speech and writing) and another with Down syndrome. Furthermore, this article published in CACIC 2023 proposes reflecting on the best resources for empathising. The present work extends the article published in CACIC 2023, expanding with more detail the conceptual framework that frames the empathising guideline and enriching the descriptions of the two experiences. In addition, this present work adds recommendations regarding possible resources to be used in each guideline's item. We hope that this work will contribute to accessible software design.